PERBANDINGAN ALGORITMA LUCY-RICHARDSON DAN WIENER DALAM MEMPERBAIKI CITRA KABUR (BLUR) - Yeka Hendriyani (JURNAL AKADEMIKA)
The aimed of this research is to compare two algorithms, Wiener and Lucy-Richardson in order to restore blurred image. The tested image that is used in the experiment is randomly chosen from a set of images that is often used in digital image processing. Then the chosen image is given two kinds of blur effect which are Gaussian and motion blur which have different level of blur. After the blur effect is given, the degradation image is restored using Wiener and Lucy-Richardson algorithm. The restored images are compared with the original images to calculate the pixel error. From the experiment, it is found that Wiener algorithm is better than Lucy-Richardson in order to restore blurred image in case of Motion and Gaussian Blur.